Effects of training at altitude on anaerobic distance and critical velocity - Hodgdon, J. A.; Vickers, R. R.; Sucec , A. A. (Naval Health Research Centre, 1996)
A work capacity model has been proposed as a means of estimating both aerobic and anaerobic capacities from a series of performance measures. The relationship between power and time is modeled as a rectangular hyperbola offset by an amount reflecting a power output which theoretically can be maintained indefinitely (pcrit). Additionally, the amount of work that can be performed at levels above pcrit is fixed and referred to as the anaerobic work capacity (wan). Moritani and coworkers have shown for 2 subjects that pcrit, but not wan is decreased when the fraction of inspired O2 (fio2) is decreased. This study attempted to extend these findings using run time measures collected as part of a study of training at altitude. Run times for distances of 1609, 3218, and 4,828 m were recorded at sea level (140 m) 5 days prior to (pre) travel to 2440 m altitude, within 5 days of arrival at 2440 m (alt), and within 5 days of return to sea level (rtn) for 19 college track athletes (13 male, 6 female). Values for critical velocity (vcrit) and aerobic distance (dan) were determined for each individual at each session (pre, alt, and rtn) as the intercept and slope, respectively of the linear least squares regression of running velocity on the inverse of run time for the three performance runs. Vcrit was used as a estimate of pcrit in the model and dan as an estimate of wan. There was a variation in vcrit with session (p<0.001). Vcrit was smaller at altitude than at sea level. There was also a small but significant (p<0.01) increase in vcrit at rtn compared to pre. Vcrit differed between genders (p<0.001), but there was no gender by session interaction. Dan also varied with session (p<0.001) having decreased values at altitude relative to sea level. There were no differences in pre and rtn values for dan, no gender differences, and no gender by session interaction. Vcrit findings were in keeping with those of Moritani and coworkers, although there appears to be a difference in the magnitude of the effect of decreased oxygen tension which bears further investigation. The decrease in dan is at variance with the findings of Moritani and coworkers, but may be explained in terms of the role of oxygen in lactate metabolism or incomplete acid-base balance adjustment to altitude.